PENGARUH PENGGUNAAN MEDIA SPIN THE WHEEL QUIZ TERHADAP KEMAMPUAN MEMBACA INTENSIF SISWA PADA MATA PELAJARAN BAHASA INDONESIA KELAS IV B SD INPRES WAIOTI - Maria Jesika Lipat Uran; Sonya Kristiani Maria; Genoveva Lise Dua Kowe (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study was motivated by the low intensive reading skills of fourth-grade students in Bahasa Indonesia at SD Inpres Waioti. The limited use of engaging learning media caused students to be less active and less focused in understanding reading texts. This study aimed to determine the effect of using the spin the wheel quiz media on students' intensive reading skills in Bahasa Indonesia for Grade IV B at SD Inpres Waioti. This research employed a quantitative approach using a pre-experimental One Group Pretest–Posttest Design. The sample consisted of 20 fourth-grade students. Data were collected through tests and observations. The research instruments included pretest and posttest questions as well as an observation sheet. Data were analyzed using the normality test and the Paired Sample t-test with the assistance of IBM SPSS Statistics version 27. The results showed that the students' mean pretest score increased from 67.10 to 89.60 on the posttest. The hypothesis testing revealed a Sig. (2-tailed) value of 0.000 < 0.05, indicating that H₀ was rejected and Hₐ was accepted. In addition, the observation results showed an average achievement of 95.83%, which was categorized as very good. Therefore, the use of the spin the wheel quiz media had a significant positive effect on the intensive reading skills of fourth-grade students in Bahasa Indonesia at SD Inpres Waioti.